2001
DOI: 10.3201/eid0705.010529
|View full text |Cite
|
Sign up to set email alerts
|

Jamestown Canyon Virus: Seroprevalence in Connecticut

Abstract: (bla PER-1 and bla VIM-2 ) had been detected separately among clinical isolates, underscores the possibility of the emergence of new threatening combinations of resistance determinants among nosocomial pathogens. In fact, the recruitment of similar resistance determinants within a single P. aeruginosa strain can determine a resistance phenotype to virtually all the available antipseudomonal beta-lactams, an occurrence that can be particularly dramatic when, as in the present case, resistance to beta-lactams is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…This conclusion is in agreement with an antibody prevalence rate of 21% in white-tailed deer populations (Zamparo et al 1997) and human seroprevalence rates ranging from 3.9% to 10.1% (Mayo et al 2001) in Connecticut. Virus infection in mosquitoes occurs throughout the season, from June through September, and it closely parallels mosquito abundance, with peak infection rates extending from mid-June through mid-July.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This conclusion is in agreement with an antibody prevalence rate of 21% in white-tailed deer populations (Zamparo et al 1997) and human seroprevalence rates ranging from 3.9% to 10.1% (Mayo et al 2001) in Connecticut. Virus infection in mosquitoes occurs throughout the season, from June through September, and it closely parallels mosquito abundance, with peak infection rates extending from mid-June through mid-July.…”
Section: Discussionsupporting
confidence: 86%
“…cantator collected from a limited number of sites in the south central, coastal region of the state (Sprance et al 1978, Main et al 1979, Andreadis et al 1994. A seroprevalence rate of 21% was found in an analysis of sera from hunter-killed white-tailed deer collected in the state in 1993 (Zamparo et al 1997), and a corresponding survey of human sera from blood donations made in 1990 and 1995 (Mayo et al 2001) revealed seroprevalence rates ranging from 3.9% to 10.1%. In 2001, the first confirmed human case of JCV infection was diagnosed from a hospitalized teenage patient with illness onset in late August (Nelson et al 2002).…”
mentioning
confidence: 94%
“…3,34,[37][38][39][40][41] The geographic distribution of our cases was similar, mostly in the northern contiguous United States, but some of our case patients resided in areas where human JCV infections have not previously been documented (e.g., Idaho, Massachusetts, Mississippi, New Hampshire, Oregon, Pennsylvania, and Rhode Island). Wisconsin reported the most cases during our study period.…”
Section: Discussionmentioning
confidence: 76%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] JCV neutralizing antibodies have been found in various mammals throughout mainland North America, 13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and identified in humans throughout the United States. [1][2][3][4][5]34,[37][38][39][40][41] JCV is a member of the California serogroup viruses, which include La Crosse virus (LACV), California encephalitis virus, and snowshoe hare virus. 42 Although the presence of anti-JCV immunoglobulin (Ig) M detected by enzyme-linked immunosorbent assay (ELISA) is usually evidence of a recent JCV infection, it also may indicate infection with another closely related California serogroup virus.…”
mentioning
confidence: 99%
“…California encephalitis virus was originally isolated in 1941 [100], and while the group of diseases are named after this virus, it is relatively rare with disease occurrence mainly located in the western United States and Canada. While La Crosse and California encephalitis viruses cause the vast majority of disease in children, Jamestown Canyon virus affects predominantly the elderly in regions of the northern United States with seroprevalence in some areas reaching 10% [101]. …”
Section: California Encephalitis Group (Lacrosse Virus) (Family: Bunymentioning
confidence: 99%